Empowerment of Waria Ludruk Artists in AIDS/HIV Prevention Program - Maimunah, Maimunah; Aribowo, Aribowo (Universitas Negeri Semarang, 2015)
Waria or transgender is one of the key population which has a significant role in the success of HIV/AIDS prevention program in East Java. It is estimated that the biggest waria community is in East Java, particularly in Surabaya. The main objective of this research is improving capacity building of ludruk artist waria through HIV/AIDS prevention program. The study has two objectives; firstly to find the effective strategies in improving wariaâ€™s feminine skills such as knitting, hair dressing. Secondly to find the effective programs both on-stage and off-stage to improve the quality of ludruk performance such as revitalizing their marketing management, using social media to promote their schedule to the young generation. Some inportant points can be conluded from this study. Firstly, integrated coordinating system between ludruk artist waria and waria communities such as Perwakos and Iwama should be improved. HIV/AIDS prevention programs become uneffective without coordination. In this point, ludruk artist waria need to know that HIV/AIDS prevention programs such as VCT, HIV testing is free of charge. Secondly, in terms of management internal system, ludruk needs to revitalize the content of the story in their performance to be more compatible with the younger audience. To do so, the cooperation is needed among all the stakeholeders to make ludruk survive in the capitalist industrial show business in Indonesia.Salah satu populasi kunci yang memberi kontribusi tingginya prevalensi HIV dan AIDS di JATIM adalah komunitas waria karena di propinsi ini estimasi jumlah waria terbesar di Indonesia. Penelitian ini akan membahas bagaimana waria seniman ludruk dilibatkan dalam pencegahan HIV/AIDS. Program yang telah dilakukan adalah revitalisasi baik on-stage (diatas panggung) dan off-stage (di luar panggung). On-stage memfokuskan pada upaya revitalisasi pertunjukan ludruk dengan sistem dan manajemen pertunjukan yang lebih modern, menarik penonton generasi muda dan memanfaatkan tekhnologi internet dalam pemasarannya. Sedangkan Off-stage melalui penguatan keterampilan feminine (feminine skills) seperti menjahit, salon, wirausaha dll sehingga mereka mandiri secara ekonomi. Hasil penelitian menyimpulkan ada faktor internal yaitu kurangnya koordinasi pimpinan ludruk dengan organisasi induk waria dalam mensosialisasikan program penanggulangan HIV/AIDS. Disamping itu, mobilitas waria yang tinggi antar kota menjadi kendala tersendiri untuk mengumpulkan mereka ketika ada pemeriksaan VCT dan tes HIV. Faktor internal ludruk adalah perlunya revitalisasi dan inovasi managemen pemasaran yang modern berbasis tekhnologi serta inovasi cerita ludruk agar lebih menjangkau anak muda. Dibutuhkan kerjasama dengan semua stakeholders agar ludruk tetap bertahan dalam gempuran industri hiburan di Indonesia.Â